REVITALIZING THE CICADAS TRADITIONAL MARKET WITH A CONTEMPORARY VERNACULAR ARCHITECTURAL APPROACH - Amat Rahmat (Jurnal Scientia, 2022)
The market is a place or place for buying and selling a product, managers and presenters, a place for interacting or buying and selling that develops and is required to be able to follow the development of an increasingly sophisticated era. This Cicadas Traditional Market is a facility or container that is quite important to support shopping in the city of Bandung. The purpose of this design is to provide understanding and knowledge of the revitalization of the Cicadas Traditional Market with a Contemporary Vernacular Architecture Approach with the application of the theme 'Contemporary Vernacular Architecture'. Contemporary Vernacular Architecture is an architectural theme that seeks to minimize adverse effects on the natural and human environment and produce a better and healthier place to live, which is done by utilizing energy and natural resources efficiently and optimally. Application of the Contemporary Vernacular Architecture Theme in the Cicadas Traditional Market building Contemporary Vernacular Architecture, is an architectural style designed according to local needs, availability of building materials, and reflects local traditions.